Implementasi Pelayanan Publik Berbasis HAM di Kantor Imigrasi Kelas II Non TPI Ponorogo - Mahyuda Dwi Maheswara; Robby Darwis Nasution; Yusuf Adam Hilman; Jusuf Harsono (Spirit Publik: Jurnal Administrasi Publik, 2022)
The role of human rights in government has a major influence on the ongoing activities carried out by government officials in a country to achieve state goals. However, it is undeniable that there are still human rights violations in the performance of public services. Given the importance of human rights-based public services provided to the community, so it is often used as an indicator of the success of a government regime. With conditions that have not been maximized, especially in human rights-based services, in order to realize good governance, where accountability is one of the principles that must be met in governance. It is hoped that this research can describe the implementation of human rights-based public services. This research on human rights-based public services uses a qualitative descriptive method with the type of research that describes, describes, or describes the state of the object under study as it is, according to the situation and conditions when the research was conducted. Based on the research results, the implementation of human rights-based public services at the Immigration Office Class II Non TPI Ponorogo has been carried out in accordance with the human rights-based public service standards set out in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 2 of 2022.